2023
DOI: 10.1111/phc3.12898
|View full text |Cite
|
Sign up to set email alerts
|

Taking Risks on Behalf of Another

Abstract: A growing number of decision theorists have, in recent years, defended the view that rationality is permissive under risk: Different rational agents may be more or less risk-averse or risk-inclined. This can result in them making different choices under risk even if they value outcomes in exactly the same way. One pressing question that arises once we grant such permissiveness is what attitude to risk we should implement when choosing on behalf of other people. Are we permitted to implement any of the rational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…If charitable giving should be thought of as a collective enterprise, then we should treat the status quo as including only contingencies that exist apart from our collective intervention, and ask about the difference that our collective charitable giving will make to the (risk-weighted and ambiguity-resolved expected) good. There are again three See also the overview of views in Thoma (2023).…”
Section: What Attitudes Should We Adopt In Our Charitable Giving?mentioning
confidence: 99%
“…If charitable giving should be thought of as a collective enterprise, then we should treat the status quo as including only contingencies that exist apart from our collective intervention, and ask about the difference that our collective charitable giving will make to the (risk-weighted and ambiguity-resolved expected) good. There are again three See also the overview of views in Thoma (2023).…”
Section: What Attitudes Should We Adopt In Our Charitable Giving?mentioning
confidence: 99%
“…In contrast to this suggestion, numerous studies have shown that doctors’ own risk attitudes, rather than those of their patients, affect the clinical decisions they make 46–48. Meanwhile, in a parallel body of emerging literature about making risky decisions on behalf of others, which is not specific to medical contexts, philosophers adopt a range of positions about what risk attitude ought to be adopted 24 49–56…”
Section: Risk Attitudes and Deferencementioning
confidence: 99%
“…Note that this description of risk attitudes is stated only in terms of the resultant preferences, but there is ongoing debate about exactly what sort of attitude risk attitudes are, and how to model these in theories of rational choice (see Thoma 24 for a helpful overview). I will remain neutral on these contentious matters here, as I intend for the arguments herein to apply to different conceptions and formal representations of risk attitudes.…”
Section: Risk Attitudes and Deferencementioning
confidence: 99%